2018
DOI: 10.1039/c8dt02190b
|View full text |Cite
|
Sign up to set email alerts
|

Precise size control of layered double hydroxide nanoparticles through reconstruction using tripodal ligands

Abstract: Precise size control of layered double hydroxide nanoparticles (LDHNPs) is crucial for their applications in anion exchange, catalysis, and drug delivery systems. Here, we report the synthesis of LDHNPs through a reconstruction method, using tripodal ligands (e.g., tris(hydroxymethyl)aminomethane; THAM). We found that the mechanism of reconstruction at least includes a dissolution-recrystallization process rather than topotactic transformation. THAM is immobilized on the surface of recrystallized LDHNPs with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 69 publications
0
14
0
1
Order By: Relevance
“…Tris-NH 2 was used both as a base for coprecipitation of LDHNPs and as a modifier. In our previous studies, MgAl LDHs and metal hydroxides were modified with tripodal ligands by the reaction at 80 °C; thus, the interlayer-modified CoAl LDHNPs were synthesized at this temperature at the first time. Because no solid product precipitated at 80 °C due to the formation of stable complexes between Co 2+ and Tris-NH 2 (Table , entry 0), the reaction solution was transferred to a tightly capped 100 mL autoclave and heated at 180 °C for 24 h. A gel precipitated in the solution after the hydrothermal treatment.…”
Section: Experimental Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tris-NH 2 was used both as a base for coprecipitation of LDHNPs and as a modifier. In our previous studies, MgAl LDHs and metal hydroxides were modified with tripodal ligands by the reaction at 80 °C; thus, the interlayer-modified CoAl LDHNPs were synthesized at this temperature at the first time. Because no solid product precipitated at 80 °C due to the formation of stable complexes between Co 2+ and Tris-NH 2 (Table , entry 0), the reaction solution was transferred to a tightly capped 100 mL autoclave and heated at 180 °C for 24 h. A gel precipitated in the solution after the hydrothermal treatment.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…We have reported that tripodal ligands (R–C­(CH 2 OH) 3 (R = NH 2 , CH 2 OH, NHC 2 H 4 SO 3 H); denoted as Tris-R hereafter) with three bonding sites form bonds stable to hydrolysis, with outer surface hydroxy groups of MgAl LDHs and the interlayer surface of various brucite-type metal hydroxides. , Although a monodentate M–O–C bond (M is a metal cation) is unstable to hydrolysis, a similar bond can be stabilized, forming a tridentate bond from a molecule. The modification proceeds in situ during the formation of LDHs without exclusion of CO 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reconstruction of an amorphous LDO back to a crystalline LDH is well-known, and this process is often referred to as “a memory effect”. , For example, during calcination of Mg 2 Al-CO 3 LDH, the layered structure collapses by dehydroxylation of the metal hydroxide layers and by interlayer carbonate ion decomposition releasing CO 2 , upon rehydration in air, the crystalline layered structure reforms with concomitant CO 2 capture from the atmosphere to form the interlayer charge compensating carbonate anions. Our earlier work indicates that reconstruction is actually a dissolution-recrystallization , process and that high aspect ratio LDH NS can be prepared using an aqueous concentrated glycine solution . Therefore, in order to gain more insight into this process we have explored if the aspect ratio of the isolated LDH nanosheets can be rationally controlled by the key process parameters such as calcination temperature and duration of reconstruction.…”
Section: Results and Discussionmentioning
confidence: 99%
“…LDHs offer a peculiar characteristic feature of the memory effect, through which the structure of LDHs can be reconstructed after calcination. [ 75 ] Despite the success, the reconstruction of LDHs often results in several shortcomings of the carbonate contamination, amorphous end product, and encapsulation of some impurities. Owing to these facts, it is highly required to apply the inert atmosphere in the reconstruction of LDHs.…”
Section: Nanoengineering Strategiesmentioning
confidence: 99%